2021
DOI: 10.18502/jri.v22i2.5801
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 Pandemic on Stress and Anxiety of Non-infected Pregnant Mothers

Abstract: Background: The newly emerging COVID-19 has caused severe anxiety around the world and it is infecting more people each day since there is no preventive measure or definite therapy for the diseases. The present study aimed to evaluate its effect on anxiety and stress of pregnant mothers during perinatal care. Methods: Three–hundred pregnant mothers without COVID–19 infection who were referred to the hospitals affiliated to Iran University of Medical Sciences for delivery during April 2020, based on negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…] 2021 China 298 N/A 54 Mappa I [ 61. ] 2021 Italy 161 p < 0.0001 55 Mehdizadehkashi A [ 62. ] 2021 Iran 300 N/A 56 Yirmiya K [ 63.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…] 2021 China 298 N/A 54 Mappa I [ 61. ] 2021 Italy 161 p < 0.0001 55 Mehdizadehkashi A [ 62. ] 2021 Iran 300 N/A 56 Yirmiya K [ 63.…”
Section: Resultsmentioning
confidence: 99%
“…] China 298 2021 Anxiety,Depression N/A Mappa I [ 61. ] Italy 161 2021 Anxiety STAI-T,STAI-S Mehdizadehkashi A [ 62. ] Iran 300 2021 Anxiety self-designed questionnaire Yirmiya K [ 63.…”
Section: Resultsmentioning
confidence: 99%
“…The pandemic created stress and anxiety in pregnant women, regardless of their infection status. 24 A recent study by Masters et al reported that 80% of pregnant women perceived increased symptoms of depression, and 88% had anxiety about the pandemic. 25 Multiple studies have confirmed that these psychological factors are associated with adverse maternal and neonatal outcomes, including preterm birth, unplanned operative delivery, low birth weight, younger gestational age, and increased neonatal morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic created stress and anxiety in pregnant women, regardless of their infection status. 24 A recent study by Masters et al reported that 80% of pregnant women perceived increased symptoms of depression, and 88% had anxiety…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…An analysis conducted by Mehdizadehkashi was dominated by respondents characterized by a high level of anxiety, of whom as many as 39% asked for an elective Cesarean section. In this same group, 86.4% of respondents felt frustrated because of the COVID-19 pandemic [ 38 ]. In the reports byMortazavi et al, the main predictor of pregnancy being concluded by Cesarean section was the pregnant woman’s fear of childbirth and the pain associated with it [ 39 ].…”
Section: Discussionmentioning
confidence: 99%